A pH-responsive emulsion stabilized by alginate-grafted anisotropic silica and its application in the controlled release of λ-cyhalothrin. (15th November 2017) - Chen, Kai; Yu, Gaobo; He, Furui; Zhou, Qingfeng; Xiao, Dunchao; Li, Jiacheng; Feng, Yuhong
Graphical abstract: Highlights: Alg-SiO2 -x samples were synthesized via the Ugi reaction. Compared with pristine SiO2 -x, modified SiO2 -x possessed obvious pH-responsive properties. Stable liquid paraffin-in-water emulsions were prepared with Alg-SiO2 -x. The results of sustained-release assay demonstrated that the emulsion is a pH-responsive drug delivery system. The sustained-release curves of λ-cyhalothrin are describable by the Weibull model. Abstract: Alginate (Alg) was grafted on the surface of anisotropic silica (SiO2 -x) via the Ugi reaction (Alg-SiO2 -1, Alg-SiO2 -2, and Alg-SiO2 -4). Compared with pristine SiO2 -x, modified SiO2 -x is more sensitive to pH. Three stable liquid paraffin-in-water emulsions were prepared with Alg-SiO2-1, Alg-SiO2-2, and Alg-SiO2-4. Alg-SiO2 -2 exhibited satisfactory emulsification ability. The emulsions became more stable as emulsion pH varied from 2.0 to 6.2 because of polymer chain interactions that led to the formation of a three-dimensional network. When the emulsion pH varied from 6.2 to 8.0, the particle charge increased, in turn increasing interparticle the electrostatic interactions that increased emulsion stability. When the emulsion pH was 9.0, the subsequent decrease in particle charge, decreased the emulsion stability. The model drug λ-cyhalothrin was embedded in the emulsions. A sustained-release assay demonstrated that increasing emulsion pH from 3.0 to 8.0 decreased cumulative drug release from the emulsion from 99.7% to 13.5%. This result indicated that the emulsion is a pH triggered drug delivery system. The sustained-release curves of λ-cyhalothrin are describable by the Weibull model.